The Making of the World How International Organizations Shape Our Future - Schemeil, Yves Prof (Verlag Barbara Budrich, 2023)
International Organizations (IOs) were designed to provide global public goods, among which security for all, trade for the richest, and development for the poorest. Their very existence is now a promise of success for the cooperative turn in international relations. Although the IO network was once created by established powers, rising states can hardly resist the massive production of norms that their governments can be reluctant to respect without being able to discard them. IOs are omnipresent, and exert great influence on the world as we know it. However, rulers and ruled are hardly aware of such compelling and snowballing processes. Yves Schemeil uses his in-depth knowledge of IOs to analyze their current impact on international relations, on world politics, and their potential of shaping the global future.